Agonistic and Antagonistic Interactions between Chlorhexidine and Other Endodontic Agents: A Critical Review - Mohammadi, Zahed; Giardino, Luciano; Palazzi, Flavio; Asgary, Saeed (Iranian Endodontic Journal, 2014)
Root canal irrigants play a significant role in elimination of the microorganisms, tissue remnants, and removal of the debris and smear layer. No single solution is able to fulfill all these actions completely; therefore, a combination of irrigants may be required. The aim of this investigation was to review the agonistic and antagonistic interactions between chlorhexidine (CHX) and other irrigants and medicaments. An English-limited Medline search was performed for articles published from 2002 to 2014. The searched keywords included “chlorhexidine AND sodium hypochlorite/ethylenediaminetetraacetic acid/calcium hydroxide/mineral trioxide aggregate". Subsequently, a hand search was carried out on the references of result articles to find more matching papers. Findings showed that the combination of CHX and sodium hypochlorite (NaOCl) causes color changes and the formation of a neutral and insoluble precipitate; CHX forms a salt with ethylenediaminetetraacetic acid. In addition, it has been demonstrated that the alkalinity of calcium hydroxide (CH) remained unchanged after mixing with CHX. Furthermore, mixing CHX with CH may enhance its antimicrobial activity; mixing mineral trioxide aggregate (MTA) powder with CHX increases its antimicrobial activity but may have a negative effect on its mechanical properties.